Penerapan Algoritma FP-Growth Dalam Pencarian Hubungan Antara Waktu Pembelian Dan Barang yang Dibeli Untuk Strategi Promosi Penjualan - Tasya Marzuqah; Inggih Permana; M Afdal (JURIKOM (Jurnal Riset Komputer), 2023)
Ledimart is a mini market that sells daily necessities. Ledimart is located in Pangkalan Kerinci District, Pelalawan Regency, Riau. The problem faced by the Ledimart minimarket is that this minimarket does not know when is the right time to carry out a promotion. To overcome these problems, this study conducted Association Rule Mining (ARM), in order to find out the relationship between the time of purchase and the goods purchased. The ARM algorithm used is the FP-Growth Algorithm. Based on the experimental results in December 2021, 6 rules were obtained, in January 2022, 6 rules were obtained, and in Ramadan 2022, 12 rules were obtained. By knowing this pattern, it is hoped that it can help Ledimart know when it is the right time to carry out promotions